Analysis of the lifestyle profile of university professors and its relationship to obesity as a risk factor for morbidity (Research, Society and Development, 2021)
Obesity represents a worrying public health problem as it is increasing exorbitantly, which, consequently, increases the risk of morbidities associated with it, in addition to being the main cause of death in people under 60 years old due to COVID-19. The aim of this study was to evaluate, through a questionnaire on the Google Forms platform, the quality of life of professors in the undergraduate courses at the University Center of Patos de Minas (UNIPAM), verifying the importance of physical exercise, both resistance and aerobic, in combating obesity as a risk factor for morbidity, as well as comparing them. This is a descriptive qualitative-quantitative cross-sectional study, carried out using Microsoft Excel 2016 and the results were presented using graphs and tables. The sample consisted of 80 university professors from UNIPAM, in which 63.7% were female and 36.3% were male. It was found that most professors, both from courses in the health area and from courses in other areas, were eutrophic, but those in the health area, relating them to BMI, are more overweight and obese, but those in this area had a larger sample (n 54). Given the data collected in the research, it is concluded that both courses have the majority of the eutrophic population, but there is still a significant amount of overweight and obesity, and only 42.5% do not have any pathology, and it is proposed that further studies are carried out for greater results and knowledge.